The Principal's Contribution through Supervision to the Effectiveness of Learning Resource Utilization - Ernawatie, Ernawatie; Berliani, Teti; Simanungkalit, Eva Marlina; Shelvia, Bet; Nanik, Nanik; Firmanto, Hezkiel Aldi (Journal of English Language and Education, 2025)
An important strategy to enhance the quality of education is by optimizing the utilization of learning resources within the educational process. This study aims to analyze the role of the principal as a supervisor in the use of learning resources at SDN Bukit Bamba 1, Pulang Pisau. This qualitative research uses a case study approach with data collection through observation, interviews, and documentation. Research informants included the principal and teachers. Data analysis was conducted using an interactive pattern that included data condensation, data presentation, and drawing conclusions. The results show that the principal has a strategic role as a supervisor in improving the quality of learning by assisting teachers in the use of learning resources. The obstacles are limited supporting facilities, limited internet access, and a lack of variety of learning media. This study recommends the need to improve infrastructure, strengthen teacher training, and develop collaborative learning communities to support more varied learning.